A MULTI-STAGE VALIDATION OF AN INTERIOR DESIGN MODEL FOR PSYCHOLOGICAL WELL-BEING - Dananjaya, Ahmad (KURVATEK, 2026)
Abstract Traditional interior design often prioritizes aesthetics over users' psychological needs, while existing Human-Centered Design (HCD) approaches remain intuitive. This research proposes and validates a "human as an element" design paradigm focused on personalization, flexibility, and autonomy. A multi-stage mixed-methods methodology was used to test its impact on psychological well-being. The first stage, a Virtual Reality (VR) experiment (N=180), found that the "human as an element" design significantly increased psychological well-being compared to a minimalist (control) design, providing causal evidence. The second stage, a pre-test/post-test field case study (N=46), implemented these principles in a real-world setting. Results showed a dramatic increase in psychological comfort, validating the model's practical effectiveness. This study bridges the gap between internal (VR) and external (field) validity, culminating in an empirically tested "Integrative Psycho-Behavioral Interior Design Model" for evidence-based practice.